2010
DOI: 10.1096/fj.08-125856
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐204/211 alters epithelial physiology

Abstract: MicroRNA (miRNA) expression in fetal human retinal pigment epithelium (hfRPE), retina, and choroid were pairwise compared to determine those miRNAs that are enriched by 10-fold or more in each tissue compared with both of its neighbors. miRs-184, 187, 200a/200b, 204/211, and 221/222 are enriched in hfRPE by 10- to 754-fold compared with neuroretina or choroid (P<0.05). Five of these miRNAs are enriched in RPE compared with 20 tissues throughout the body and are 10- to 20,000-fold more highly expressed (P<0.005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
186
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 69 publications
(99 reference statements)
14
186
0
Order By: Relevance
“…Mutation in miR-204 as the cause of the disease is consistent with the observation that miR-204 is preferentially expressed in multiple ocular tissues, including the retina, RPE, ciliary body, and lens (11)(12)(13). In addition, previous in vitro and in vivo studies in medaka fish suggested its important roles in the development and function of the retina (13,14), lens (13)(14)(15), and RPE (12).…”
supporting
confidence: 87%
“…Mutation in miR-204 as the cause of the disease is consistent with the observation that miR-204 is preferentially expressed in multiple ocular tissues, including the retina, RPE, ciliary body, and lens (11)(12)(13). In addition, previous in vitro and in vivo studies in medaka fish suggested its important roles in the development and function of the retina (13,14), lens (13)(14)(15), and RPE (12).…”
supporting
confidence: 87%
“…Particularly noteworthy was the consistent miR-204 downregulation observed in both tumor sets, specifically associated with the presence of the BRAF mutation. The targets of this miRNA were predicted to impair several cellular processes, such as those maintaining epithelial physiology, 36 which could explain the relatively poor prognosis described for these patients. 37 Another interesting marker was miR-7, highly significantly associated with BRAF mutation when compared to normal thyroid tissues in tumor set 1, and with wild-type papillary carcinomas in the validation set.…”
Section: Modern Pathology (2015) 28 748-757mentioning
confidence: 99%
“…In previous experiments we have used these primary cultures to determine the expression, polarization and function of plasma membrane transport proteins and identify specific signaling pathways that regulate RPE function [1][2][3][4][5][6][7][8][9][10][11] These characteristics as they are accumulated provide a validation set of properties that can be applied to each cell generation. The experiments summarized below identify the proteins that determine transepithelial fluid transport and the integrity of the paracellular pathway.…”
Section: Functional Validation Of Hfrpe Cell Culturementioning
confidence: 99%